ANALYSIS OF FACTORS AFFECTING THE QUALITY OF LIFE OF PROLANIS PATIENT WITH TYPE 2 DIABETES MELLITUS - Handayani, Dian; Salsabila, Jihan; Versita, Riana; Pranata, Meki (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Diabetes mellitus is an infectious disease characterized by hyperglycemia due to abnormalities in insulin secretion action or both. The goals of diabetes mellitus therapy include reducing symptoms and complications, reducing mortality, and improving the quality of life of patients with diabetes mellitus. This study aimed to provide an overview of the quality of life and the correlation between the characteristics of respondents and the quality of life of patients with type 2 diabetes mellitus who received oral antidiabetics. This study used observational analytics with a cross sectional design of 84 respondents. Patients' quality of life was measured using the Diabetes Quality of Life Clinical Trial Questionnaire (DQLCTQ). Data analysis was performed using an Independent Sample T-test. The results of this study showed that the quality of life of patients with type 2 diabetes mellitus was classified as good (56%) and there were significant differences between the two groups in the domains of health pressure, personal satisfaction, and trial effects on the DQLCTQ questionnaire; there were significant differences in BMI, duration of DM, and treatment type on the quality of life of prolanis patients with type 2 diabetes mellitus. Keywords: type 2 diabetes mellitus, quality of life, DQLCTQ